2022
DOI: 10.1029/2022gb007372
|View full text |Cite
|
Sign up to set email alerts
|

Salinity Induces Allometric Accumulation of Sulfur in Plants and Decouples Plant Nitrogen‐Sulfur Correlation in Alpine and Arid Wetlands

Abstract: Salinization alters the elemental balance of wetlands and induces variations in plant survival strategies. Sulfur (S) plays vital roles in serving regulatory and catalytic functions in stress resistance of plants. Yet, how plant S and its relationships with nitrogen (N) vary across natural environmental gradients are not well documented. We collected 1,366 plant samples and 230 water and sediment samples from 230 wetlands in Tibetan Plateau and adjacent arid regions of western China, to analyze the effects of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 65 publications
0
1
0
Order By: Relevance
“…Similarly, relatively lower LS concentrations in our study were caused by the high proportion of gymnosperms (mainly conifers), because gymnosperms contained the minimum LS concentrations of all phylogenetic taxa and thus pulled down the mean values of woody plants (table 1). The herbaceous species, especially aquatic plants, had the highest LS concentrations in all growth forms, verifying the crucial role of S in stress tolerance, because most of the aquatic plant species were collected from saline habitats in the Tibetan Plateau and arid and semi-arid regions in northwest China [25].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, relatively lower LS concentrations in our study were caused by the high proportion of gymnosperms (mainly conifers), because gymnosperms contained the minimum LS concentrations of all phylogenetic taxa and thus pulled down the mean values of woody plants (table 1). The herbaceous species, especially aquatic plants, had the highest LS concentrations in all growth forms, verifying the crucial role of S in stress tolerance, because most of the aquatic plant species were collected from saline habitats in the Tibetan Plateau and arid and semi-arid regions in northwest China [25].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, S concentrations and the correlations of S to N and P in plants should be species-specific, which are largely determined by the physiological requirements of plants and vary among species [18,19]. The variations in plant S-N-P stoichiometries can be attributed to the differences in plant taxa, as well as the local elemental conditions in environments, as demonstrated by the regional studies [12,14,[25][26][27]. However, compared with the well-documented leaf N-P stoichiometry, the globally stoichiometric patterns of plant leaf S concentrations and their relationships to N and P are less studied.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among these local adaptation genes, we further identified 33 genes under positive selection involved in abiotic stress response and plant growth and development in the NW and SW lineages (Table S17). The NW lineage is distributed in Northwest China in areas with numerous saline wetlands due to low precipitation and high evaporation together with saline soil parent materials (Zuo et al, 2022); the SW lineage is mainly found Southwest China in an environment characterized by high altitude. The identified PSGs may be related to the response of the NW and SW lineages to their environmental conditions.…”
Section: Discussionmentioning
confidence: 99%